2009
DOI: 10.1111/j.1467-7687.2009.00939.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of motion processing in children with autism

Abstract: Recent findings suggest that children with autism may be impaired in the perception of biological motion from moving point-light displays. Some children with autism also have abnormally high motion coherence thresholds. In the current study we tested a group of children with autism and a group of typically developing children aged 5 to 12 years of age on several motion perception tasks, in order to establish the specificity of the biological motion deficit in relation to other visual discrimination skills. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
89
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 33 publications
5
89
2
Order By: Relevance
“…This discrepancy is in accordance with growing evidence that, while common in ASD, abnormalities in motion perception are not universal and may affect only sub-types of individuals with the condition (e.g. Milne et al 2006;Annaz et al 2010).…”
Section: Patterns Of Motion Perception In Asdsupporting
confidence: 86%
See 1 more Smart Citation
“…This discrepancy is in accordance with growing evidence that, while common in ASD, abnormalities in motion perception are not universal and may affect only sub-types of individuals with the condition (e.g. Milne et al 2006;Annaz et al 2010).…”
Section: Patterns Of Motion Perception In Asdsupporting
confidence: 86%
“…Impairment of this integration has indeed been reported in ASD (Spencer et al 2000;Milne et al 2002;Pellicano et al 2005;Milne et al 2006;Tsermentseli et al 2008;Atkinson 2009). In addition, individuals with ASD show deficits in the discrimination of biological motion (Blake et al 2003;Parron et al 2008;Klin et al 2009;Annaz et al 2010) and in the recognition of emotions from body movements (Hubert et al 2007;Atkinson 2009), both often tested with "point-light displays" (PLDs) of actions (Johansson 1973). The ability to extract social information from PLDs is an indication that complex social cognition can be performed on the basis of basic perceptual input (Adolphs, 2003), and thus, reduced sensitivity to PLDs of emotions has often been taken as evidence for compromised social functioning in ASD.…”
mentioning
confidence: 99%
“…There is no guarantee that an impairment observed early in childhood is necessarily obvious in later childhood or adulthood. For example, we have recently shown that there are no behavioural differences between a group of adolescents with ASD and typically developing controls on a test of biological motion perception, even though the same test revealed significant differences between younger ASD and typically developing controls (Annaz, et al 2010;Jones, et al, Submitted). Further experiments will be needed to examine whether the lack of attentional bias for biological motion is found earlier in infancy in ASD.…”
Section: Discussionmentioning
confidence: 98%
“…There is now growing evidence that children with ASD are less sensitive in their perception of briefly presented and masked biological motion point-light displays (Annaz et al 2010;Blake et al 2003;Kaiser et al 2010a, b) indexed by the increased signal to noise ratio needed for children with ASD to detect biological motion. Could a lack of preferential looking toward biological motion be the result of a less sensitive perception of the stimuli?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation